Faktor-Faktor Pendukung dan Penghambat Semangat Belajar Siswa: - Harahap, Ade Chita Putri; Anggina, Asih; Ritonga, Dahniar; Amarta, Muhammad Aji; Ayumi, Salshainbila; Rahmi, Wardatur; Mariana, Wina; Rahman Nst, Yeni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The enthusiasm for student learning is important in an effort to support students in their learning achievements both in academic and non-academic achievements. The failure of students is a concern for researchers to see the background which is a source of enthusiasm for learning for students. Based on the results of the researcher's research, the researcher saw many cases where students had low interest in learning because there was no enthusiasm for learning from within the students. This research will examine the inhibiting and supporting factors that become the enthusiasm for student learning at SMK Mandiri Medan. The method used in this research is a qualitative method. Where the researcher made direct observations and conducted interviews with several students as samples. Based on the results of the study, the researchers found several factors that supported students' enthusiasm for learning including high motivation, enthusiasm, a sense of accomplishment and a desire to develop. Meanwhile, the inhibiting factors in the enthusiasm for learning in class XII students at SMK Mandiri Medan include a non-conducive learning environment, lack of support for students, excessive pressure and demands. Keywords: students, enthusiasm, learning